The Effect of Remote Sensing Resolution Limits on Aeolian Sandstone Measurements and the Reconstruction of Ancient Dune Fields on Mars: Numerical Experiment Using the Page Sandstone, Earth. Issue 12 (3rd December 2019) - Cardenas, Benjamin T.; Swanson, Travis; Goudge, Timothy A.; Wagner, R. Wayne; Mohrig, David
Abstract: The distribution of cross‐set thicknesses is important data for reconstructing ancient aeolian dune fields from the strata they accumulated, but most aeolian strata on Mars must be observed from satellite. We hypothesize that remote sensing resolution limits will affect cross‐set thickness measurements and the dune‐field reconstructions that follow. Here we test this hypothesis using a numerical experiment mimicking the effects of satellite image resolution limits performed on a distribution of aeolian cross‐set thicknesses measured in the field from the Jurassic Page Sandstone, Arizona, USA. Page set thicknesses are exponentially distributed, representing the accumulations of dry dune fields (no water table interactions with the dunes) in a state of net‐sediment bypass. When observed from satellite, set‐thickness measurements increase as adjacent sets become indistinguishable, based on the map‐view distance between their upper and lower bounding surfaces. This is termed the exposure distance of a cross set and is a function of (1) the set thickness, (2) the dip of the outcrop surface, and (3) the number of satellite image pixels required to detect a set (detection limit). By running experiments using outcrop dips from 1° to 60° and detection limits from 0.75 to 2.50 m (3 to 10 High‐Resolution Imaging Science Experiment pixels), we find that gently sloping surfaces (< 13°) at all detection limits are associated with the least blending of adjacent sets, conserving the net‐bypass interpretation made from the true set thicknesses. Although these results are specific to the Page, they can be used as a guide for future Mars work. Plain Language Summary: Cross sets are sedimentary deposits left by wind‐blown sand dunes. Cross sets can be preserved for long amounts of time as sedimentary rocks, where variability in their thickness can be analyzed to understand the motion of ancient dunes and the processes that helped the dunes move, including ancient winds, the presence or lack of near‐surface groundwater, ancient topography, and tectonics. On Earth, we can accurately measure cross‐set thicknesses in the field, but for Mars we are mostly limited to satellite images. Here we mimic the uncertainties present in a satellite image of Mars by altering field‐measured thicknesses from Earth. We perform this numerical experiment on field‐measured cross‐set thicknesses from the Page Sandstone, Arizona. The altered thicknesses are checked for how they might affect our understanding of the ancient Page dune fields. Based on these experiments, satellite images offer a risk of misinterpretation, but good measurements can be made at High Resolution Imaging Science Experiment image resolution if the slope of the rock outcrop is shallow, 13° from horizontal or less. At these shallow slopes, the thinnest cross sets are exposed over long distances, making them detectable from orbit. Though these results are specific to the Page, they can help guide future Mars work. Key Points: The perceived thicknesses of aeolian cross sets are increased (and their distributions altered) due to remote sensing resolution limits Image resolution limits can severely alter interpretations of aeolian sandstones, even at HiRISE resolution (best available at 25 cm/pixel) Accurate measurements from HiRISE images require outcrop slopes less than 13°, such that thin sets are exposed over detectable distances